Periodontal infection as a risk factor for preterm low birth weight - Gandhimadhi D; Mythili R (Wolters Kluwer Medknow Publications, 2010)
Introduction: There is an overwhelming body of evidence strongly suggesting that periodontal infection may have a significant negative impact on pregnancy outcome in some women. The aim of this study was to determine the association, if any, between periodontal disease and preterm low birth weight. Materials and Methods : A total of 211 mothers between the ages of 17 and 35 were grouped into two categories based on the gestational age and weight of the baby as cases (< 37 weeks, < 2500 g) and controls (>37 weeks, >2500 g). Relevant obstetric history and information on other primary risk factors for preterm low birth weight were obtained. Investigation reports on blood group, Rh factor and hemoglobin (Hb) were also gathered. Oral assessments included: simplified oral hygiene index (OHI-S), gingival bleeding index, probing pocket depth and clinical attachment level (CAL). Results: Cases had significantly more attachment loss and probing pocket depth, poor oral hygiene, more percentage of sites with attachment loss (Extent) and more mean attachment loss per site (Severity) and less Hb than controls. The number of visits for prenatal care and the percentage of sites with CAL≥2mm (Extent 2) remained significant when compared to other variables. Conclusion: The study indicated that periodontal disease is a contributing factor for preterm low birth weight.